Integration of Indonesian Character Values in Educational Management at the Indonesian School of Makkah, Saudi Arabia - R. Sinsin Rosyidin; Lia Yuliana; A. Saeful Bahri (Journal of Islamic Education Students (JIES), 2026)
The phenomenon of students’ character degradation amid the challenges of globalization, technological advancement, and complex social environments necessitates the strengthening of systematically and integratively managed character education. This study aims to analyze the implementation of character education management at Sekolah Indonesia Makkah through a management-function approach integrated with learning components. The research employed a qualitative method with a case study design. Data were collected through interviews, observations, and document analysis involving the principal, teachers, homeroom teachers, guidance and counseling services, and relevant stakeholders. The findings indicate that planning is conducted by integrating core ethical values into the school’s vision, mission, curriculum, regulations, as well as co-curricular and extracurricular programs. Organizing and implementation are supported by a clear division of roles, the cultivation of school culture, literacy programs, supervision, and a measurable reward and punishment system. Monitoring is carried out through classroom supervision, integrated oversight, and evaluation of teacher performance and student development. Supporting factors include institutional commitment and a conducive environment, while challenges remain in optimizing evaluation instruments and ensuring consistent implementation. This study proposes an integrated and sustainable input–process–output conceptual model of character education management.